(untitled) (JIMLY LEGAL YUSTISIA JOURNAL, 2026)
The manifestation of democracy in one country is certainly not the same as in another. Democracy is the process of creating and maintaining a civil society by respecting, striving for, and realizing the values to which a society aspires. Indonesia is undergoing a dynamic process in the implementation of its democracy, and what has been done should be evaluated in the direction of a more ideal democracy. In the practice of local government administration, both in Indonesia and a number of other countries such as Australia, Belgium and Hungary, there is a wide variety of systems for filling regional head positions. However, until now there is no standard measure to determine that a system of filling regional head positions by direct election would be more democratic than an indirect election system. A system certainly has its own advantages and disadvantages. Therefore, comparing the success of the system for filling regional head positions in many countries can be a good lesson for filling the constitutional gap in the 1945 Constitution of the Republic of Indonesia.